Voltammetry of Electrochemically Reversible Systems at Electrodes of Any Geometry: A General, Explicit Analytical Characterization - Molina, A; Gonzalez, J; Henstridge, M; Compton, R (2011)
A general, explicit analytical solution for volta-mmetry using any multipotential waveform for an electrochemically reversible system at an electrode of any geometry is derived. This expression has special physical relevance in the case of electrodes and microelectrodes which possess nonuniform current densities such as disks and bands, where analytical descriptions of voltammetry are confined to predictions of limiting currents. We have applied our analytical expressions to normal pulse voltammetry, staircase cyclic voltammetry, and cyclic voltammetry for disks, spheres, bands, and cylinders. The results have been validated against those obtained by using numerical simulation with the agreement found to be excellent. © 2011 American Chemical Society.